Designing an electronic ticketing system (E-Ticketing) for crossing transportation in Indonesia using an Object-Oriented Analysis and Design (OOAD) approach - Aeng Anwar Sanusi; Lily Sutandi; Zakky Ahmad Djamaluddin (Jurnal Mantik, 2023)
The purpose of this research is to analyze and design an electronic ticket system for ferry crossings in Indonesia and to analyze and design a passenger boarding pass system for ferry passengers in Indonesia. The method used in this study using literature and observation. The results of this study indicate that First, development of an electronic ticketing system (E-Ticketing) for ferry transportation modes can be a solution to help the public to obtain information and purchase transactions for ferry transport tickets in Indonesia. Second, the development of an electronic ticketing system (E-Ticketing) for crossing modes of transportation can be a solution to the problem of collecting manifest data for ferries in Indonesia. Third, development of an electronic ticketing system (E-Ticketing) for crossing modes of transportation can make it easier for people to cancel or change travel schedules. Fourth, the development of an electronic ticketing system (E-Ticketing) for crossing transportation modes requires electronic financial transaction services.